PECULIARITIES OF THE MASTICATORY APPARATUS OF GUINEA PIGS (Cavia porcellus) - Constantin SPATARU; Mihaela-Claudia SPATARU (Journal of Applied Life Sciences and Environment)
Guinea pigs (Cavia porcellus) are rodents that feed on grassy plants, buds and sprouts, with cheek teeth having specialised abrasive surfaces for plant grinding. In analysing the prehension and trituration ways of guinea pigs, many differences concerning mandible conformation, the positioning of cheek teeth and the morphology of the masticatory muscles compared to other rodents were found. Masticatory muscles of guinea pigs are predominant compared to the mimetic muscles which are reduced. Compared to other rodents, in guinea pigs, inside the tendon thickness of the superficial part of the masseter muscle there are two rounded cartilaginous structures such as sesamoids. The dorsal one is larger, measuring about 3–4 mm in diameter having the role of reducing pressure on the tendon when it passes over the mandible ridge. The other is ventrally placed, about 2–3 mm in size and protects the tendon of the superficial part of the masseter muscle when it passes over the ventral tubercle of the mandible.